A ROLE OF ENVIRONMENTAL FACTORS ON CALCIUM SIGNALING GENES IN NEUROSPORA CRASSA - Gedela, Ravi (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Neurospora crassa possesses a complex of Ca2+_signaling system consisting of 48 Ca2+-signaling proteins. The Ca+2-signalling protein plays an important role in a range of processes such as a Ca2+ stress tolerance, hyphal tip branching growth, cytoskeletal organization, cell cycle progression, circadian clocks, sporulation, sexual development, and ultraviolet (uv) survival. The environmental factors, broadly defined to include chemical, physical, nutritional, and behavioral factors...etc. In this article, we are reporting here a role of physic-chemical environmental factors pH, glucose and ultraviolet (UV) affect on ∆NCU06366, and ∆NCU05225 Ca2+ -signaling knockout mutants in N. crassa. The verified result showed that, ∆NCU06366 and ∆NCU05225 Ca2+ -signaling knockout mutants slower growth rate at pH (7.6), and glucose starvation against to the control wild type respectively. In addition to that the found results showed, ultraviolet (UV) survival, there is no UV radiation affects on ∆NCU06366 and ∆NCU05225 Ca2+-signaling knockout mutants as evaluate to the positive and the negative controls in N.crassa. Along with that, In-silico analysis Multiple sequence analysis and Phylogenetics tree for conserve domain of NCU05225 (NADH dehydrogenase) and NCU06366 (Ca2+/H+ anti-porter) Ca2+-signaling genes encodes proteins in N.crassa, showed high sequence similarity and 68-100% and 89% homology to the other class of fungi respectively. It indicates that, NCU05225 (Mitochondrial NADH dehydrogenase) and NCU06366 (Ca2+/H+ exchangers) Ca2+-signaling gene encoding conserve domain widespread in other class of fungi as well.